Penile block for paediatric urological surgery: A comparative evaluation with general anaesthesia - Panda, Aparajita (Medknow Publications & Media Pvt Ltd, 2011)
AIM: Peri-operative pain relief in children can be provided by conventional general anaesthesia or by regional nerve blocks. The present study was carried out to evaluate and compare the effectiveness of penile block for penile surgery with the standard technique of general anaesthesia (GA) of short duration of less than two hours, and also to evaluate the postoperative pain relief obtained by penile block. MATERIALS AND METHODS: The study was carried out in the department of Anaesthesiology and Intensive care of our hospital, on 60 children in the age group of 1-10 years, belonging to American Society of Anesthesiologists (ASA) grades I and II, and divided randomly into two groups: Group B and group G, comprising of 30 patients each. Group B children received a penile block whereas group G children underwent a standard general anaesthetic procedure. Baseline, intra-operative and post-operative heart rate (HR), electrocardiogram (ECG), non-invasive blood pressure (NIBP) (systolic and diastolic) and pulse oximeter oxygen saturation (SpO(2)) were recorded at regular intervals. The duration of post-operative pain relief, time to rescue analgesia and time to first feed were also evaluated and recorded. Statistical analysis was carried out using statistical package for social sciences (SPSS) 11 version for windows and employing analysis of variance (ANOVA), unpaired student t test, Chi-square test and Mann Whitney U test for various parameters. Value of P<0.05 was considered as significant and P<0.0001 as highly significant. RESULTS: The demographic characteristics were comparable in both the groups. Heart rate, systolic blood pressure, diastolic blood pressure and pulse oximetry showed remarkable differences at various time intervals during intra-operative and post-operative period, which were statistically significant on comparison (P<0.05 and P<0.0001). Post-operative pain relief, time to first rescue analgesia and time to first feed also showed statistically significant differences. CONCLUSIONS: Penile block is very effective when used along with light sedation for distal penile surgeries of less than 2 hours duration as compared to standard GA as reflected by more stable haemodynamics in peri-operative period, excellent pain relief extending up to 6-8 hrs postoperatively and absence of any significant complications or side effects.